(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: To conceptualise a sustainable defence financing model by embedding green finance principles into maritime security frameworks in the Indo-Pacific, where ecological vulnerability and geopolitical pressures are intensifying. Study Design/Methodology/Approach: A descriptive qualitative approach is adopted to explore secondary sources comprising policy documents, multilateral reports, and scholarly literature. Institutional Theory and Resource-Based Theory guide the analytical lens to examine how legitimacy, regulatory adaptation, and internal capacities shape green-oriented defence mechanisms. Findings: Defence financing strategies that align with ESG principles offer a pragmatic response to regional instability and environmental threats. Key mechanisms identified include the issuance of green bonds, development of low-emission technologies, ESG-based procurement criteria, and collaborative financing through regional platforms. Successful integration depends on institutional coherence and innovation capacity across defence and financial sectors. Originality/Value: Introduces a novel intersection between green finance and defence strategy within Indo-Pacific policy discourse. Provides an interdisciplinary model that reframes defence financing as both a geopolitical instrument and a sustainability lever, offering actionable insights for national governments, financial institutions, and multilateral bodies.